Planktonic ostracods (Myodocopa: Halocyprididae) from abyssopelagic depths in the Atlantic, North Pacific and Gulf of Oman: Chavturia abyssopelagica (n. gen., n. sp.), alocypretta profunda (n. sp.), Halocypretta parvirostrata Chavtur and Stovbun, 2008 and Halocypretta striata (Müller, 1906) - Angel, Martin V. (Zootaxa, 2013)
A novel species and genus of halocyprid ostracod, Chavturia abyssopelagica, and a new species of Halocypretta are described from depths >3000 m in the Atlantic. The new genus is related to Halocypretta, itself a genus that has only recently been described from deep waters in the North Pacific. Supplementary observations are made on the type species, Halocypretta parvirostrata, based on additional specimens from the North Pacific. Halocypretta striata from the Gulf of Oman is reported for the first time since it was first described and is redescribed in detail. All four species are illustrated and compared using a set of meristic characters.